Willingness to Pay for Orange-fleshed Sweet Potato Juice: A Comparison of Rural and Urban Consumers in Kenya - Owuor, Antonate Akinyi; Otieno, David Jakinda; Okello, J.J.; Oluoch-Kosura, Willis (Informa UK Limited, 2022)
Bio-fortified foods including orange-fleshed sweet potato (OFSP) have been promoted worldwide as a potential mechanism to combat Vitamin A deficiency. One of the ways to promote consumption of OFSP is to process it into less perishable products with wider geographical coverage. However, there is a dearth of empirical insights on the specific attributes that consumers desire in such value-added products; this constrains sustainable investments in such initiatives. In order to fill this knowledge gap, the current study assessed consumers' willingness to pay for OFSP juice attributes in rural and urban areas using choice experiment approach. Results showed that on average, for each liter of OFSP juice, rural consumers were willing to pay premiums of USD0.58, 0.39, 0.66, 0.75 and 0.72 respectively for the juice with OFSP only or that with OFSP and lemon as opposed to that with OFSP and mango; OFSP juice with additives; origin labeling of the OFSP juice and; joint inspection and certification of the OFSP juice rather than public inspection and certification. On the contrary, rural consumers demanded a discount of USD0.25 for involvement of private rather than public entities in the inspection and certification process. The urban consumers on the other hand, were willing to pay USD0.93, 0.82, 2.22, 0.32, 0.54 and 0.76 respectively, for juice with OFSP only or that with OFSP and lemon instead of OFSP and mango; additives, origin labeling and; private or joint inspection and certification as opposed to public inspection of the juice. These findings should inform the design of OFSP juices that meet the heterogeneous preferences of the rural and urban consumers.